Self-healing group key distribution scheme with revocation based on dual directional hash chain - DU Chun-lai1; HU Ming-zeng2; ZHANG Hong-li2; ZHANG Dong-yan2 (Tongxin xuebao)
A self-healing group key distribution scheme with revocation in MANET using dual directional hash chain was proposed.The association relation between different session keys was built.By means of broadcast information and own secrets,the legal nodes which lost some legal session keys due to network faults could be capable of recovering such lost session keys on their own,without requiring additional transmission from the group manager.The group manager could revoke the group nodes by revocation polynomial.Node was endowed with a set of masking secret according to its life-cycle.Through the security and efficiency analysis,the key distribution scheme reduces communication cost and storage cost yet still achieves security property.